Risk-Based Defense Planning in Archipelagic States: Strategic Analysis, Methodological Framework, and Technological Integration in the Indo-Pacific - Revila Oulina; Guntur Eko Saputro; Sutanto Sutanto (Journal of Social Work and Science Education, 2026)
The volatile security environment of the Indo-Pacific demands that defense institutions adopt adaptive planning approaches beyond conventional threat-based models. This qualitative study examines Risk-Based Defense Planning (RBDP) implementation in archipelagic states, which face distinctive security challenges from dispersed territories, extensive maritime boundaries, and persistent sea blindness. Through systematic literature review and comparative analysis of defense planning frameworks in Indonesia and the Philippines, the study evaluates risk assessment methodologies including Multi-Criteria Decision-Making approaches specifically Fuzzy Analytic Hierarchy Process and Failure Mode and Effects Analysis for objective defense resource prioritization. The analysis also examines NATO’s Risk-Based Framework for Strategic Planning as a reference model. Findings reveal three key patterns: (1) archipelagic states are shifting toward risk-oriented defense strategies, evidenced by the Philippines’ Comprehensive Archipelagic Defense Concept and Indonesia’s Global Maritime Fulcrum vision; (2) emerging technologies—Maritime Domain Awareness systems, unmanned vehicles, and low-earth orbit satellites are critical for situational awareness and risk mitigation; and (3) effective RBDP requires integration of military and non-military policies within total defense frameworks, supported by regional cooperation. The study contributes a synthesized RBDP framework for archipelagic contexts and offers policy recommendations for addressing hybrid threats, maritime security challenges, and climate-related risks. Limitations include the focus on two case countries and reliance on secondary sources.